Analisis hambatan pembelajaran dalam jaringan (daring) pada mata pelajaran ips peserta didik kelas v di sekolah dasar - Aulia Diah Rahmawati; Siti Istiyati; Siti Kamsiyati (Universitas Sebelas Maret, 2022)
This study aims to: (1) describe the barriers to the online learning process in social studies subjects experienced by teachers and students of grade-V SD Negeri 1 Krasak Boyolali, (2) describe solutions in overcoming the barriers of teachers and students in the online learning process at grade-V social studies subjects at SD Negeri 1 Krasak Boyolali. This study is a qualitative descriptive study. Research subjects include V-grade teachers, 10 V-grade students, principals. Data collection is conducted using passive participating observation techniques, document analysis and in-depth interviews. The validity test technique used is triangulation of methods and data sources. Data analysis techniques using interactive analysis techniques. The results of the research that have been carried out are that the obstacles that occur in the learning process are in the planning of teachers not making lesson plans because of the difficulty in preparing media and methods so that they use offline lesson plans. Barriers in the implementation of the application used, internet connection, implementation of media, implementation of methods, delivery of materials, facilities, assignments. Barriers to attitude assessment because teachers cannot meet directly with students. It can be concluded that in online learning, there are obstacles in the planning, implementation, and assessment.. So there are solutions to overcome obstacles by establishing communication between teachers regarding technology in online learning, the role of parents in supporting online learning activities, the time gap in task collection, the same assessment system.